Actively open-minded thinking: development of a shortened scale and disentangling attitudes towards knowledge and people. (2nd January 2018) - Svedholm-Häkkinen, Annika M.; Lindeman, Marjaana
ABSTRACT: Actively open-minded thinking (AOT) is often used as a proxy for reflective thinking in research on reasoning and related fields. It is associated with less biased reasoning in many types of tasks. However, few studies have examined its psychometric properties and criterion validity. We developed a shortened, 17-item version of the AOT for quicker administration. AOT17 is highly correlated with the original 41-item scale and has highly similar relationships to other thinking dispositions, social competence and supernatural beliefs. Our analyses revealed that the AOT is not a unitary construct, but comprises four distinct dimensions, some of which concern attitudes towards knowledge, and others concern attitudes towards people. This factor structure was replicated in another data-set, and correlations with other measures in four data-sets (total N = 3345) support the criterion validity of these dimensions. Different dimensions were responsible for the AOT's relationships with other thinking dispositions.